MILITERE BESKERMING VAN STAATSHOOFDE: AGTERGROND EN HERKOMS - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
An Institution such as the State President’s Guard, has a long history and goes back to antiquity. Famous examples are the guards of King Xerxes of Persia and of more recent origin, the Swiss guard of the Vatican City. In the modern world these guards are the rule rather than the exception, in most states. The article below looks into the origin, functions and duties of inter alia the English Guard and the French Guard and the requirements for admission into these units. Also the origin and variations of the uniforms of these guards are dealt with. The female guards employed by the King of Siam deserve to be mentioned because of their unusualness and the author then proceeds to examine the Swiss Guard of the Vatican City. This article serves as an introduction to the articles that follow, dealing with the State President’s unit in the Republic of South Africa.